Spatial Analysis of the Level of Digitalization of the Information Society in the Selected European Macroregion - Katarzyna ZEUG-ZEBRO (Communications of International Proceedings, 2021)
Development of the ICT sector can boost economic growth, innovation and competitiveness of the economy and increase employment. The ICT infrastructure is inextricably linked to the Internet and the possibilities of its dissemination, ie. the technical availability and the access cost of Internet connections as well as the cost of Internet equipment. A relevant marker of the development level in an information society is Internet access and its use in households and companies. The paper offers the analysis of the spatial dependence of Internet access in Europe using spatial statistics. The paper also presents the results of linear and non-linear ordering of European macroregions according to the level of Internet access, obtained using the Hellwig and Ward methods. The study used empirical material that came from the resources of the European Statistical Office (Eurostat). All calculations and maps were made in Mathematica and the statistical program R CRAN.
Keywords: Information society; Hellwig’s method; Ward’s method; spatial analysis